A systematic review of the role of vitamin D and calcium in premenstrual syndrome - Fatemeh Abdi; Gity Ozgoli; Fatemeh Sadat Rahnemaie (Obstetrics & Gynecology Science, 2019)
Premenstrual syndrome (PMS) is a common disorder that affects millions of women of reproductive age worldwide. In recent years, there has been a focus on finding accessible, acceptable, and cost-effective therapeutic approaches with minimal side effects to treat the symptoms of PMS. This systematic review aimed to investigate the role of calcium and vitamin D in Premenstrual syndrome. The PubMed, EMBASE, Web of Science, Scopus, Science Direct, and Google Scholar databases were systematically searched for relevant articles from clinical trial, case-control, and cross-sectional studies. The Strengthening the Reporting of Observational Studies in Epidemiology checklist was used to assess the quality of the selected papers. A total of 28 eligible high-quality papers were reviewed. Low serum levels of calcium and vitamin D during the luteal phase of the menstrual cycle were found to cause or exacerbate the symptoms of PMS. Therefore, the administration of calcium and vitamin D supplements or the use of a diet rich in these two substances can restore serum levels and eliminate or reduce the symptoms of PMS. Calcium and vitamin D supplementation are recommended as an inexpensive, low-risk, acceptable, and accessible approach to eliminate or reduce the symptoms of PMS.